Shared Intelligence for smart grids management - Praça, Isabel (2016)
Making smart grids and microgrids an overwhelming and successful reality implies the consideration of a lot of challenges coming from different domains and collaboration is a keyword to seize the high ground. SEAS Shared Intelligence (SEAS SI) is a platform for algorithms sharing and execution developed under the scope of Smart Energy Aware Systems (SEAS) project to promote the intelligent management of smart grids and microgrids, by means of the shared usage of algorithms and tools, while ensuring code and intellectual protection. In this paper the platform goals and architecture will be described, and a case study based on SEAS-SI available algorithms, EVeSSi and FreqReg, will be presented. The case study aims at highlighting the collaborative management relevance allowing the simulation of the dynamic behavior of a huge number of electric vehicles while addressing the frequency regulation service for the smart grid.